2020
DOI: 10.1038/s41598-020-61844-z
|View full text |Cite
|
Sign up to set email alerts
|

Right-lateralized fronto-parietal network and phasic alertness in healthy aging

Abstract: Phasic alerting cues temporarily increase the brain's arousal state. In younger and older participants, visual processing speed in a whole report task, estimated based on the theory of visual attention, is higher in cue than no-cue conditions. The present study assessed whether older participants' ability to profit from warning cues is related to intrinsic functional connectivity (iFC) in the cingulo-opercular and/ or right fronto-parietal network. We acquired resting-state functional magnetic resonance imagin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Thus, when all stimuli are task relevant, as in whole-report paradigms, increased alertness will boost all processing rates, resulting in a proportional increase in VPS. Consistent with this, other findings have shown that VPS increases following psychostimulant intake (Finke et al, 2010) and phasic alerting cues (Haupt, Ruiz-Rizzo, Sorg, & Finke, 2020), in which alerting-cue intensity monotonically increased only the VPS parameter C and not other TVA parameters (Petersen, Petersen, Bundesen, Vangkilde, & Habekost, 2017). Thus, we hypothesized that targeted, computerized tonic-alertness training would also increase VPS in healthy older adults.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Thus, when all stimuli are task relevant, as in whole-report paradigms, increased alertness will boost all processing rates, resulting in a proportional increase in VPS. Consistent with this, other findings have shown that VPS increases following psychostimulant intake (Finke et al, 2010) and phasic alerting cues (Haupt, Ruiz-Rizzo, Sorg, & Finke, 2020), in which alerting-cue intensity monotonically increased only the VPS parameter C and not other TVA parameters (Petersen, Petersen, Bundesen, Vangkilde, & Habekost, 2017). Thus, we hypothesized that targeted, computerized tonic-alertness training would also increase VPS in healthy older adults.…”
supporting
confidence: 81%
“…The linkage identified between higher CON functional connectivity and higher VPS gain from a longer term intervention differs from functional connectivity–VPS benefit relationships established in previous studies on the effects of short-term auditory phasic-alertness cues. In these studies, higher cuing gains were found to be related to lower CON functional connectivity in younger adults and to lower functional connectivity in the right frontoparietal network in older adults (Haupt et al, 2020). The discrepancies between the current findings and these results might reflect differences in the brain systems underlying phasic and intrinsic alertness functions.…”
Section: Discussionmentioning
confidence: 98%
“…For each frequency bin, we obtained the ICs' spatial cross‐correlation values with resting‐state network templates (Allen et al., 2011) using FSL's fslcc command (https://surfer.nmr.mgh.harvard.edu/pub/dist/freesurfer/tutorial_packages/OSX/fsl_501/src/avwutils/fslcc.cc). As we were interested only in networks previously shown relevant for VPS (Haupt et al., 2020; Ruiz‐Rizzo et al., 2018), we selected the two ICs, as defined in Allen et al., (2011), that showed the highest correlation coefficients with, correspondingly, COn (Allen et al's Salience, IC 55), RFPn (Allen et al's IC 60), and visual networks (Allen et al's IC 39, IC 46, IC 48, IC 59, IC 64, and IC 67). Note that we did not exhaustively select all brain networks relevant for attention (e.g., the dorsal attention network or the bilateral executive control network) but only those that have been specifically associated with VPS.…”
Section: Methodsmentioning
confidence: 99%
“…Most patients performed well in the task, however, one patient performed poorly and withdrew early from the experiment. This experience prompted us to question how well ECoG mapping would perform in a less demanding task, which might be particularly relevant when applying ECoG mapping in pediatric populations, patients with low general cognitive ability (Ruiz-Rizzo et al, 2018 or patients who are otherwise unable or unwilling to engage in demanding cognitive testing (Haupt et al, 2020;Ruiz-Rizzo et al, 2020). Our cognitive experiment included a passive condition in which the same auditory stimuli were presented without any explicit task.…”
Section: Influence Of Attention On Auroc Valuesmentioning
confidence: 99%